Global distribution of potential impact hotspots for marine plastic debris entanglement - Marthe A. Høiberg; John S. Woods; Francesca Verones (Ecological Indicators, 2022)
Marine animals have been known to interact with and become entangled in plastic debris for decades. Despite increasing annual input volumes of plastic waste to the natural environment and the threat this constitutes to marine biodiversity, impacts of mismanaged plastic waste generally remain unquantified in environmental impact assessments. In this paper, we develop a Species Sensitivity Distribution (SSD) approach for estimating a spatially differentiated indicator of potential macroplastic entanglement impacts with global coverage of the world’s oceans. This constitutes a key modelling step that contributes towards the inclusion of plastic litter effects in impact assessments. We gathered entanglement incidence data for 20 species of marine mammals, turtles and birds from different populations and marine regions. To capture species-specific sensitivities to entanglement and spatially varying concentrations of plastic debris, concentration–response modelling of field data was used to develop the SSD-based model. This was achieved by linking population specific entanglement records to corresponding regional areas of exposure and an existing global model of plastic debris concentrations. The SSD was further applied to derive an estimate of the Potentially Affected Fraction (PAF) of species on a global scale, highlighting regional hotspots of potential entanglement impacts at current levels of marine plastic pollution. This indicator can be adapted and applied in impact assessments in order to account for potential impacts of mismanaged plastic waste ending up in marine ecosystems.